Knockdown of endoplasmic reticulum chaperone BiP leads to the death of parvocellular AVP/CRH neurons in mice. (19th December 2022) - Kawaguchi, Yohei; Hagiwara, Daisuke; Tsumura, Tetsuro; Miyata, Takashi; Kobayashi, Tomoko; Sugiyama, Mariko; Onoue, Takeshi; Yasuda, Yoshinori; Iwama, Shintaro; Suga, Hidetaka; Banno, Ryoichi; Grinevich, Valery; et al.
Abstract: Arginine vasopressin (AVP) is expressed in both magnocellular (magnAVP) and parvocellular AVP (parvAVP) neurons of the paraventricular nucleus, and AVP colocalizes with corticotropin‐releasing hormone (CRH) only in the parvocellular neurons. The immunoglobulin heavy chain binding protein (BiP) is a major endoplasmic reticulum (ER) chaperone which regulates the unfolded protein response under ER stress. We previously demonstrated that knockdown of BiP in magnAVP neurons exacerbated ER stress, which resulted in the autophagy‐associated cell death of magnAVP neurons. Using the same approach, in the present study we examined the role of BiP in mouse parvAVP/CRH neurons. Our data demonstrate that BiP is expressed in mouse parvAVP/CRH neurons under nonstress conditions and is upregulated in proportion to the increase in CRH expression after adrenalectomy. For BiP knockdown in parvAVP/CRH neurons, we utilized a viral approach in combination with shRNA interference. Knockdown of BiP expression induced ER stress in parvAVP/CRH neurons, as reflected by the expression of C/EBP homologous protein. Furthermore, BiP knockdown led to the loss of parvAVP/CRH neurons after 4 weeks. In summary, our results demonstrate that BiP plays a pivotal role in parvAVP/CRH neurons, which function as neuroendocrine cells producing a large number of secretory proteins. Abstract : This study revealed that the expression of BiP (an ER chaperone) in parvAVP/CRH neurons is upregulated in response to increased CRH synthesis following ADX. Furthermore, BiP knockdown in parvAVP/CRH neurons induced ER stress and cell death in CRH neurons. Taken together, these results demonstrate that BiP has an essential role in the survival of parvAVP/CRH neurons.